Role of emodin to prevent gastrointestinal cancers: recent trends and future prospective - Falak Thakral; Bhairav Prasad; Rippin Sehgal; Saurabh Gupta; Ujjawal Sharma; Bikram Jit Singh; Bunty Sharma; Hardeep Singh Tuli; Shafiul Haque; Faraz Ahmad (Discover Oncology)
Abstract Gastrointestinal malignancies are responsible for approximately 35% of all cancer-related deaths, underscoring the critical need to explore pharmacologically active molecules for chemoprevention. Emodin (1,3,8-trihydroxy-6-methylanthraquinone), a natural compound derived from traditional Chinese and Japanese medicine, has recently garnered significant attention for its potential anticancer properties. Emodin exerts its chemoprotective effects through a combination of antioxidative, anti-inflammatory, and anti-proliferative mechanisms. Research indicates that emodin inhibits cancer metastasis, disrupts cell cycle progression, and impairs cancer cell survival. These effects are mediated through the activation of the p38 MAPK/JNK1/2 signaling pathway, the upregulation of pro-apoptotic factors such as Bax/Bcl-2 and caspases, and the enhancement of reactive oxygen species (ROS) levels (Supplementary Fig. 1). To optimize emodin’s therapeutic potential, it is crucial to further investigate its underlying mechanisms of action and develop advanced nano-targeted delivery systems to enhance its bioavailability. This review highlights emodin’s promise as a chemopreventive agent for gastrointestinal cancers and emphasizes its potential for development into a novel clinical formulation.